Expert reviewsSignificance of antiplatelet therapy in emergency myocardial infarction treatment - Komosa, Anna; Lesiak, Maciej; Siniawski, Andrzej; Mularek-Kubzdela, Tatiana; Grajek, Stefan (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Antiplatelet drugs play a crucial role in the treatment of patients with myocardial infarction, particularly in association with percutaneous coronary intervention. Their main advantage is the reduction of adverse ischemic incidents and the major disadvantage is the increase in the frequency of hemorrhages. Thus, the choice of appropriate drug depends on the right risk assessment of the development of these complications in individual patients. The aim of this article is to provide an update of antiplatelet therapy in emergency myocardial infarction treatment. Currently, the most important role in the process of platelet inhibition is played by ADP P2Y12 blockers: clopidogrel, prasugrel and ticagrelor. Clopidogrel and prasugrel belong to thienopyridines, and ticagrelor, a drug of irreversible action, is an analogue of adenosine triphosphate. By 2011 clopidogrel, alongside aspirin, had the highest recommendations of world cardiology associations for acute coronary syndrome treatment. The position on clopidogrel was changed following the publication of European Society of Cardiology guidelines for STEMI in 2012 which advocate the administration of acetylsalicylic acid (ASA) and ADP receptor blocker (in combination with ASA). It needs to be stressed that prasugrel and ticagrelor received class IB recommendation, while clopidogrel received only IC. However, the most recent studies aimed at introducing a new generation of antiplatelet drugs of high efficacy in prevention of ischemic incidents and of reversible action: cangrelor and elinogrel, which raise hopes for better prognosis for myocardial infarction patients.